The Relationship of Covid-19 Pandemic Anxiety with Ante-Natal Care Examination at Sei Semayang Puskesmas, Sunggal District, Deli Serdang Regency - Ninsah Putri Br Sembiring; Juliana Munthe; Henny Rista; Laria Simamora; Srilina Br Pinem; Yanti Farida Saragih (Institute of Computer Science (IOCS), 2022)
The Corona Virus (Covid-19) is a non-natural disaster that increases deaths that have an impact on Indonesia's social economy. This makes pregnant women feel anxious. Ethiopia, Nigeria, Senegal, South Africa, Uganda, and Zimbabwe have a high prevalence of mental anxiety problems including pregnant women (25.6%) and postpartum mothers (19.8%). Anxiety disorders can interfere with the growth and contraction of uterine muscles, affecting both mother and baby. This study aims: to determine the relationship between COVID-19 pandemic anxiety and pregnancy check-ups at the Sei Semayang Health Center, Sunggal District, Deli Serdang Regency. Research Population: The population is all elements / research subjects of pregnant women at the Sei Semayang Health Center, Sunggal District, Deli Serdang Regency as many as 33 samples. Research Type: This research is in the form of an analytic survey, using a cross sectional with Ante Natal Care (ANC) with sampling through interviews with respondents using a questionnaire called primary data and documenting data collection from the annual report of the Sei Semayang Health Center, Sunggal District, Deli Serdang Regency. The results of the study: The relationship between Covid-19 pandemic anxiety and Ante Natal Care (ANC) examination with a p value 0.006